“Modelo de gestión para la producción y comercialización de quinua en la parroquia Mulalillo, cantón Salcedo, provincia de Cotopaxi en el año 2020” - Gordillo Mantilla, Rosa Adriana (2021)
The elaboration of the Project "Management model for the production and commercialization of quinoa in the Mulalillo parish, Salcedo canton, Cotopaxi province in the year 2020", is presented as an alternative to solve problems of the small quinoa producer regarding the proper management of the process production, the lack of producers organization and the intervention of intermediaries in the commercialization, the model integrates the elements of the value chain and articulates the participation of the different public actors responsible for the execution of public policy in the territory and private actors as a collection option to guarantee the commercialization at a fair price, in order to achieve the productive and commercial efficiency of quinoa, thus improving the economic income of the small producers of the parish, the qualitative research methodology applied through observation and interview allowed to develop the description of the object of study, while the experimentation applied in the exercise of the production process allowed to validate the efficiency of the proposed model. The model includes the introduction of technological elements, both in the production process, for example, the use of drones for certain agricultural activities such as fertilization and fumigation, as well as in the commercialization process, through the implementation of a web page whose content aims to position the product on the market and provide information of interest for the consumer.